Electrical conductivity measurements on ice cores from the Canadian Arctic: An analysis of signal variation within and between ice cores. - Zheng, Jiancheng. (University of Ottawa (Canada), 1996)
Two ice cores, A93.1 and A93.2, drilled two meters apart at the Agassiz Ice Cap in May of 1993, had on site electrical conductivity measurements (ECM) carried out to determine the confidence limits of the ECM method for chronological and stratigraphic control. Four ECM profiles have been produced from the two cores, one directly on unprepared surfaces of A93.1 and A93.2 and two on a prepared surface of the A93.1 made by a band saw and subsequently planed by a clean microtome knife. The correlation analysis between the two ECM series of whole length ice core on A93.1 prepared and unprepared surfaces gives a correlation coefficient of 0.842. The correlation analysis of whole length of A93.1 and A93.2 cores on the unprepared surfaces gives a coefficient of 0.644. Review of multi-ice core records including $\delta{\sp }$O, ECM and melt percentage, shows that ice on the Agassiz Ice Cap of Canadian High Arctic is continuous from present to the earlier Holocene. (Abstract shortened by UMI.)
Keywords: Geology.